2009
DOI: 10.1139/b08-096
|View full text |Cite
|
Sign up to set email alerts
|

Mistletoe ecophysiology: host–parasite interactionsThis review is one of a collection of papers based on a presentation from theStem and Shoot Fungal Pathogens and Parasitic Plants: the Values of Biological Diversitysession of the XXII International Union of Forestry Research Organization World Congress meeting held in Brisbane, Queensland, Australia, in 2005.

Abstract: Mistletoes are highly specialized perennial flowering plants adapted to parasitic life on aerial parts of their hosts. In our discussion on the physiological interactions between parasite and host, we focus on water relations, mineral nutrition, and the effect of host vigour. When host photosynthesis is greatest, the xylem water potential of the host is most negative. To maintain a flux gradient and avoid stomatal closure and wilting, the mistletoe must tolerate a more negative water potential than the host. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(44 citation statements)
references
References 18 publications
2
39
0
3
Order By: Relevance
“…[1] is an evergreen plant with functional chlorophyll, capable of fixing atmospheric carbon dioxide and, therefore, considered to be a semi-parasite (hemi-parasite) [2,3]. It penetrates the tree branches, taking up water and mineral nutrients [2,4,5] through the endophytic system which consists of the haustoria and sinkers that reach the host cambium, and cortical strands that provided lateral spread [6]. Mistletoe grows mainly on branches, and rarely on trunks of woody species [7].…”
Section: Introductionmentioning
confidence: 99%
“…[1] is an evergreen plant with functional chlorophyll, capable of fixing atmospheric carbon dioxide and, therefore, considered to be a semi-parasite (hemi-parasite) [2,3]. It penetrates the tree branches, taking up water and mineral nutrients [2,4,5] through the endophytic system which consists of the haustoria and sinkers that reach the host cambium, and cortical strands that provided lateral spread [6]. Mistletoe grows mainly on branches, and rarely on trunks of woody species [7].…”
Section: Introductionmentioning
confidence: 99%
“…This exacerbates drought stress of trees especially in water-deficit areas (Glatzel & Geils, 2009), leading to growth loses and accelerated mortality by such secondary factors as fungi and bark beetles (Hawksworth & Wiens, 1996). Mistletoe can also be responsible for reduced seed production and low wood quality in the host plants (Hawksworth & Wiens, 1996;Muir & Hennon, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have clearly shown the effects of mistletoe on tree growth (Bilgili et al, 2020;Kanat et al, 2010), wood anatomy (Gol et al, 2018;Ozturk et al, 2019), biology (Mutlu et al, 2016b;Persoh et al, 2010), physiology (Ehleringer et al, 1986;Glatzel & Geils, 2009;Mutlu et al, 2016a) and morphology (Rigling et al, 2010) of host plants. In addition, the relationship between leaf area and sapwood area have been examined and documented in many broadleaved (Meadows & Hodges, 2002) and conifer species (Bancalari et al, 1987;Waring et al, 1982) including Scots pine (Albrektson, 1984;Berninger & Nikinmaa, 1994;Whitehead, 1978).…”
Section: Introductionmentioning
confidence: 96%
“…The transpiration rate and stomatal conductance of mistletoes are higher than those of hosts (Mathiasen et al, 2008;Ullmann et al, 1985). Drought stress exacerbated by mistletoes (Glatzel & Geils, 2009) and coupled by higher transpiration rate developing with decreasing xylem water potential in host branches lead to reduced photosynthetic rate of host (Mathiasen et al, 2008). Therefore, increased growth loss (Barbu, 2012;Bilgili et al, 2020;Bilgili et al, 2018;Ozturk et al, 2019), altered resource allocation (Tinnin & Knutson, 1980) and mortality (Rigling et al, 2010) are the typical results of mistletoe infection.…”
Section: Introductionmentioning
confidence: 99%